PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI INTRINSIK TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UP3 MAKASSAR SELATAN - Nuryuli Nuryuli Nuryuli (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2026)
This study aims to analyze the influence of transformational leadership style and intrinsic motivation on employee performance at PT PLN (Persero) UP3 Makassar Selatan. Using a quantitative approach with a causality design, this study involved the entire population of 50 employees as respondents through a total sampling technique. Partial test results (t-test) show that transformational leadership style (t = 3.887; sig = 0.000) and intrinsic motivation (t = 5.082; sig = 0.000) have a positive and significant effect on employee performance. Simultaneously (F-test), both variables significantly influence performance with an F-value of 27.768. The R Square value of 0.542 indicates that these two independent variables contribute 54.2% to employee performance, while the remaining 45.8% is influenced by other factors outside this study.Keywords: Transformational Leadership Style, Intrinsic Motivation, Employee Performance.